Use of calcium sulfate in inorganic mortar systems based on aluminous cement and granulated blast furnace slag to increase load values.

JP2025506916AActive Publication Date: 2025-03-13HILTI AG
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2024551893
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-08
Filing Date
2023-02-28
Publication Date
2025-03-13
Estimated Expiration
2043-02-28

Smart Images

  • Figure 2025506916000001
    Figure 2025506916000001
  • Figure 2025506916000002
    Figure 2025506916000002
  • Figure 2025506916000003
    Figure 2025506916000003
Patent Text Reader

Abstract

The present invention relates to the use of calcium sulfate in an inorganic mortar system comprising a cured aqueous phase aluminous cement component A and an initiator component B in the aqueous phase for starting the curing process, for chemical fixing of anchoring means in mineral substrates, component A further comprising at least one blocking agent selected from the group consisting of boric acid, phosphoric acid, metaphosphoric acid, phosphorous acid and phosphonic acid, and water, and component B comprising blocked granulated blast furnace slag, water and optionally at least one mineral filler.Furthermore, the present invention relates to the use of calcium sulfate in inorganic mortars for increasing load values ​​and reducing shrinkage, and to a method for chemical fixing of anchoring means, preferably metal elements, in mineral substrates such as brickwork, concrete, permeable concrete or structures made of natural stone.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the use of calcium sulfate in an inorganic mortar system for chemical fixing of fastening means in mineral substrates, comprising a cured aqueous phase aluminous cement component A and an initiator component B in the aqueous phase for starting the curing process, component A further comprising at least one blocking agent selected from the group consisting of boric acid, phosphoric acid, metaphosphoric acid, phosphorous acid and phosphonic acid, and water, and component B comprising blocked granulated blast furnace slag, water and optionally at least one mineral filler. In particular, the present invention relates to the use of calcium sulfate in an inorganic mortar system for chemical fixing of fastening means in mineral substrates to increase the load value and reduce shrinkage. Furthermore, the present invention relates to a method for chemical fixing of fastening means, preferably metal elements, in mineral substrates such as brickwork, concrete, permeable concrete or structures made of natural stone. [Background technology]

[0002] There are many inorganic mortar systems, sometimes referred to as kit-of-parts, in which the components are mixed before use or during application to start the curing process and are intended to provide good chemical fixation of the anchoring means in the mineral matrix. For example, when fast hardening is desired, organic systems based on free radically polymerizable resins are used. However, such systems are generally known to be polluting, expensive, potentially dangerous and / or toxic for the environment and for the people who handle them, and they often need to be specially labeled. Moreover, organic systems often show a significant decrease in stability when exposed to strong sunlight or otherwise thermally at high temperatures, thereby reducing their mechanical performance with respect to the chemical fixation of the anchoring means.

[0003] To overcome these shortcomings, mainly mineral systems based on alumina cement have been developed. Alumina cement has monocalcium aluminate as its main component and is widely used in the building and construction industry because the final product shows a high level of mechanical performance over time. Alumina cement is also resistant to bases, achieves maximum strength more quickly than Portland cement, and can withstand solutions of sulfates. Therefore, alumina cement systems are preferably used in the field of chemical fixation.

[0004] Furthermore, calcium aluminate slurries are known to provide high fire resistance at anchorage points. However, compared to resin-based anchoring mortars, the setting of such systems is rather slow, which requires longer waiting times on site and often interrupts the workflow. This is especially important for anchoring applications where immediate loading is crucial. In addition, calcium aluminate-based mortars are characterized by the presence of the metastable hydrate phase CAH 10 and C 2 AH 8 Stable hydrate C 3 AH 6 These materials undergo a transformation resulting in a decrease in performance over time due to their transformation into

[0005] In EP 2 162 410 a two-component system is described, which comprises a part A based on an aqueous phase alumina cement retarded by boric acid or its salts, and a part B for initiating the curing process. The initiator in part B is made only of lithium salts. In EP 0 081 385 a two-component system is also disclosed, which comprises an aqueous high alumina cement composition with inhibited setting and a reactivator composition containing lithium salts. In EP 2 794 510 a stabilized aqueous suspension is described, which comprises an alumina cement and / or calcium sulfoaluminate cement, which is inhibited by phosphorus-containing compounds and can be stored for a sufficient time even at high temperatures. The stabilized aqueous suspension can serve as a base for surface coatings.

[0006] However, these aqueous alumina cement suspensions retarded by boric acid or its salts are often not very stable for a sufficient period of time for storage before use. Moreover, boric acid is highly toxic and ecotoxic. Furthermore, these state-of-the-art systems require high water-to-cement ratios and are characterized by their undesirable conversion, which reduces their performance over time.

[0007] German Patent No. 2311239 describes an adjuvant composition for improving the setting and hardening properties of alumina cements and mortars, comprising lithia, a water-soluble lithium salt, and a hydroxylated organic acid or its salt or ester. The fluid may be directly incorporated into the alumina cement or into the mortar and concrete during their manufacture or added to the mixing water during application. However, a drawback of this system is that the cement composition and the activator composition cannot be stored for a sufficient time to be ready for use, and therefore must be freshly prepared before use depending on the desired setting and hardening time, resulting in more procedural steps before application. In addition, the lithium-based activator component is expensive, its extraction is problematic from a humanitarian, economic and political point of view, and has a high carbon dioxide footprint.

[0008] Therefore, there is a need for a ready-to-use multi-component system, preferably an inorganic system, that is superior to the systems of the prior art in terms of environmental aspects, health and safety, handling, storage time, sustainability, and a good balance between setting and hardening of the mortar. Furthermore, it is of interest to provide a system that can be used for chemical fixing of anchoring means in mineral substrates without adversely affecting the handling, properties and mechanical performance of the chemical anchoring system, as well as to provide a system that uses a lower water-to-cement ratio and conversion, which increases performance over time. Finally, there is a need for a system with a low carbon dioxide footprint, as well as an improved durability due to volume stability, and therefore does not exhibit shrinkage cracks, and in particular a system with increased load values.

[0009] In view of the above, it is an object of the present invention to provide a multi-component system, in particular an inorganic mortar system, which overcomes the drawbacks of the systems of the prior art, in particular an inorganic mortar system which is ready to use, easy to handle, environmentally friendly, can be stably stored for a certain period of time before use, presents a good balance between setting and hardening, still has good mechanical performance with regard to chemical fixing of the anchoring means even under the effect of elevated temperatures, is further characterized by the ability to reduce carbon dioxide emissions, water-to-cement ratios and conversion, and in particular presents increased load values.

[0010] It is further an object of the present invention to provide an inorganic mortar system which can be used for the chemical fixing of preferably metallic elements of an anchoring means in mineral substrates such as brickwork, concrete, permeable concrete or structures made of natural stone, as well as to provide a method for fixing said anchoring means.

[0011] These and other objects which will become apparent from the ensuing description of the invention are solved by the invention as set forth in the independent claims. The dependent claims relate to preferred embodiments.

[0012] Summary of the Invention In one aspect, the present invention relates to the use of a calcium sulfate inorganic mortar system comprising a cured aqueous phase aluminous cement component A and an initiator component B in the aqueous phase for starting the curing process, component A further comprising at least one blocking agent selected from the group consisting of boric acid, phosphoric acid, metaphosphoric acid, phosphorous acid, and phosphonic acid, and water, and component B component B comprises blocked granulated blast furnace slag, water, and optionally at least one mineral filler. In particular, component B comprises granulated blast furnace slag and a blocking agent selected from the group consisting of gluconic acid, glycolic acid, phosphonic acid, salts and esters thereof, glucose, and mixtures thereof.

[0013] In another aspect, the present invention relates to the use of calcium sulfate in inorganic mortar systems for chemical fixing of anchoring means in mineral substrates to increase their load values.

[0014] In another aspect, the invention provides an inorganic mortar system used for chemical fixing of preferably metallic elements of an anchoring means in a mineral substrate such as brickwork, concrete, permeable concrete or structures made of natural stone, and in another aspect a method for fixing said anchoring means and a method for fixing said anchoring means. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The following terms and definitions are used in the context of the present invention. As used in the context of the present invention, the singular forms "a" and "an" also include the respective plural forms unless the context clearly dictates otherwise. Thus, the terms "a" or "an" are intended to mean "one or more" or "at least one," unless otherwise specified.

[0016] The term "aluminous cement" in the context of the present invention refers to calcium aluminate cement, which consists mainly of hydrated active calcium aluminate. Another name is "high aluminous cement" or in French "Ciment fondu". The main active ingredient of calcium aluminate cement is monocalcium aluminate (CaAl 2 O 4 , CaO·Al 2 O 3 , or CA in cement chemical notation.

[0017] The term "initiator" in the context of the present invention refers to a compound or composition that modifies the chemical environment to initiate a specific chemical reaction. In the present invention, the initiator modifies the pH value of the mortar suspension, thereby deblocking the hydraulic binder in the final mix.

[0018] The term "binder" or "binder component" in the context of the present invention refers to the calcium-aluminate based cementitious component and other additional optional components such as, for example, fillers. In particular, the term "main binder component" refers to component A.

[0019] Surprisingly, the inventors have found that the addition of calcium sulfate to the inorganic mortar system according to the invention results in an easy-to-handle ready-to-use system for chemically fixed anchoring means in mineral substrates, thereby resulting in a significant increase in load values ​​when compared to systems without calcium sulfate. Furthermore, the addition of calcium sulfate reduces the shrinkage to a considerable extent, thereby ensuring a reliable application of anchoring. In particular, it has been found that the addition of calcium sulfate to an aqueous slurry-based system comprising a blocked alumina component as the main binder component and blocked ground-granulated blast-furnace slag (GGBFS) in an aqueous slurry exhibiting an alkaline pH as the second binder component results in a lower water-to-cement ratio compared to state-of-the-art inorganic component injection mortars that do not contain calcium sulfate and / or contain a filler-based activator component. In addition, it has been found that the long term strength loss due to conversion characteristic of calcium aluminate cements can be mitigated by blending these two cements with calcium sulfate to produce a stable Stratlingite hydrate phase and enhance the formation of ettringite which allows monosulfate formation, which is more stable than the calcium aluminate hydrates formed at low and intermediate temperatures and therefore also reduces conversion.

[0020] While typical calcium aluminate-based binders rely on synthetic or mined carbonate sources to mitigate strength loss due to conversion phenomena, granulated blast furnace slag is a waste product from steel production and therefore is inexpensive and has a low carbon footprint when reused as a binder. By blocking granulated blast furnace slag with sugars such as gluconate in water, an alkaline pH is achieved that can be used to activate the blocked calcium aluminate cement components. Thus, no separate activator such as sodium hydroxide or lithium hydroxide is required. The alkaline pH generated from the hydration of calcium aluminate cement subsequently activates the granulated blast furnace slag.

[0021] Furthermore, it has been found that the inorganic mortar system of the present invention does not contain any harmful substances while maintaining the standards for chemical bonding applications, and therefore also includes a reduced carbon footprint and labeling. In addition, it has been found that the use of granulated blast furnace slag in particular is more sustainable compared to the use of common Portland cement, and also has a lower carbon footprint than synthetic resins.

[0022] The present invention relates to the use of a calcium sulfate inorganic mortar system for chemically fixing an anchoring means in a mineral substrate, comprising a cured aqueous phase aluminous cement component A and an initiator component B in the aqueous phase for starting the curing process. In particular, component A further comprises at least one blocking agent selected from the group consisting of boric acid, phosphoric acid, metaphosphoric acid, phosphorous acid and phosphonic acid, and water, and component B comprises blocked granulated blast furnace slag, water and optionally at least one mineral filler.

[0023] The component A used in the present invention is based on aqueous calcium aluminate cement (CAC) or aqueous calcium sulfoaluminate cement (CAS). Calcium aluminate cements that can be used in the present invention are characterized by rapid setting and hardening, rapid drying and shrinkage compensation when mixed with calcium sulfate, and excellent corrosion and shrinkage resistance. Such calcium aluminate cements suitable for use in the present invention are, for example, Ternal® White (Kerneos, France).

[0024] Component A used in the present invention contains at least about 40% by weight, preferably at least about 50% by weight, more preferably at least about 60% by weight, and most preferably at least about 70% by weight, about 40% to about 95% by weight, preferably about 50% to about 90% by weight, more preferably about 60% to about 85% by weight, and most preferably about 70% to about 80% by weight of calcium aluminate cement, based on the total weight of component A.

[0025] The blocking agent contained in component A used according to the present invention is selected from the group consisting of boric acid, phosphoric acid, metaphosphoric acid, phosphorous acid, and phosphonic acid, preferably phosphoric acid or metaphosphoric acid, and most preferably phosphoric acid, in particular an 85% aqueous solution of phosphoric acid. Component A contains at least about 0.1% by weight, preferably at least about 0.3% by weight, more preferably at least about 0.4% by weight, most preferably at least about 0.5% by weight, about 0.1% to about 20% by weight, preferably about 0.1% to about 15% by weight, more preferably about 0.1% to about 10% by weight, most preferably about 0.3% to about 10% by weight of the blocking agent, based on the total weight of component A. In a preferred embodiment, component A contains about 0.3% to about 10% by weight of an 85% aqueous solution of phosphoric acid, based on the total weight of component A.

[0026] In advantageous embodiments, component A further comprises the following properties, either alone or in combination:

[0027] Component A may additionally comprise a plasticizer. The plasticizer may be selected from the group consisting of low molecular weight (LMW) polyacrylic acid polymers, superplasticizers from the family of polyphosphonate polyox and polycarbonate polyox, and Ethacryl superplasticizers from the polycarboxylate ether group, and mixtures thereof, such as Ethacryl™ G (Coatex, Arkema Group, France), Acumer™ 1051 (Rohm and Haas, UK), or Sika® ViscoCrete®-20 HE (Sika, Germany). Suitable plasticizers are commercially available products. Component A may contain at least about 0.2% by weight, preferably at least about 0.3% by weight, more preferably at least about 0.4% by weight, and most preferably at least about 0.5% by weight, about 0.2% to about 20% by weight, preferably about 0.3% to about 15% by weight, more preferably about 0.4% to about 10% by weight, and most preferably about 0.5% to about 5% by weight of the plasticizer, based on the total weight of component A.

[0028] Component A may additionally comprise a thickening agent. Thickening agents that may be used in the present invention may be selected from the group consisting of organic products such as xanthan gum, welan gum or DIUTAN® gum (CP Kelko, USA), mineral products such as starch-derived ethers, guar-derived ethers, polyacrylamides, carrageenan, agar, and clay, and mixtures thereof. Suitable thickening agents are commercially available products. Component A comprises at least about 0.01% by weight, preferably at least about 0.1% by weight, more preferably at least about 0.2% by weight, most preferably at least about 0.3% by weight, about 0.01% to about 10% by weight, preferably about 0.1% to about 5% by weight, more preferably about 0.2% to about 1% by weight, most preferably about 0.3% to about 0.7% by weight of said thickening agent, based on the total weight of component A.

[0029] Component A may further comprise an antibacterial agent or biocide. The antibacterial agent or biocide that may be used in the present invention may be selected from the group consisting of compounds of the isothiazolinone family, such as methylisothiazolinone (MIT), octylisothiazolinone (OIT), and benzoisothiazolinone (BIT), and mixtures thereof. Suitable antibacterial agents or biocides are commercially available products. Ecocide K35R (Progiven, France) and Nuosept OB 03 (Ashland, The Netherlands) are mentioned by way of example. Component A comprises at least about 0.001% by weight, preferably at least about 0.005% by weight, more preferably at least about 0.01% by weight, and most preferably at least about 0.015% by weight, from about 0.001% to about 1.5% by weight, preferably from about 0.005% to about 0.1% by weight, more preferably from about 0.01% to about 0.075% by weight, and most preferably from about 0.015% to about 0.03% by weight of said antimicrobial or biocide, based on the total weight of Component A. In a preferred embodiment, Component A comprises from about 0.015% to about 0.03% by weight of Nuosept OB 03, based on the total weight of Component A.

[0030] Component A may further comprise at least one mineral filler. The mineral filler that may be used in the present invention may be limestone filler, such as calcite, sand, corundum, dolomite, alkali-resistant glass, crushed stone, gravel, gravel, quartz, quartz flour, quartz sand, clay, fly ash, fumed silica, brick powder, rice peel ash, phonolite, calcined clay and metakaolin, carbonate compounds, pigments, titanium dioxide, lightweight fillers, or mixtures thereof. Suitable fillers are commercially available products. Component A may comprise at least about 1% by weight, preferably at least about 2% by weight, more preferably at least about 5% by weight, and most preferably at least about 8% by weight of the at least one filler, based on the total weight of component A.

[0031] The water content in component A is at least about 1% by weight, preferably at least about 5% by weight, more preferably at least about 10% by weight, and most preferably at least about 20% by weight, from about 1% by weight to about 50% by weight, preferably from about 5% by weight to about 40% by weight, more preferably from about 10% by weight to about 30% by weight, and most preferably from about 15% by weight to about 25% by weight, based on the total weight of component A.

[0032] The presence of plasticizers, thickeners, antimicrobials, biocides, or fillers does not change the overall inorganic nature of the cementitious component A.

[0033] Component A, which comprises the calcium aluminate cement, is present in the aqueous phase, preferably in the form of a slurry or paste.

[0034] The initiator component B used in the present invention comprises blocked granulated blast furnace slag, water and, optionally, at least one mineral filler.

[0035] Granulated blast furnace slag preferably contains 30 to 45% calcium oxide (CaO) and 30 to 45% silicon dioxide (SiO 2 ) and 1-15% aluminum oxide (Al 2 O 3 ), 4-17% magnesium oxide (MgO), and 0.5-1% sulfur (S). Further characteristic contents of granulated blast furnace slag are iron oxide (Fe 2 O 3 ), sodium oxide (Na 2 O), potassium oxide (K 2 O), chloride, sulfur trioxide (SO 3 ), and manganese oxide (Mn 2 O 3 ) which preferably represent less than 5% of granulated blast furnace slag.

[0036] Component B used in the present invention contains at least about 5% by weight, preferably at least about 10% by weight, more preferably at least about 20% by weight, and most preferably at least about 30% by weight, about 5% to about 80% by weight, preferably about 10% to about 70% by weight, more preferably about 15% to about 60% by weight, and most preferably about 20% to about 50% by weight of granulated blast furnace slag, based on the total weight of Component B.

[0037] The blocked granulated blast furnace slag of component B comprises granulated blast furnace slag and a blocking agent. The blocking agent for granulated blast furnace slag is selected from the group consisting of gluconic acid, glycolic acid, phosphonic acid, their salts and esters, glucose, and mixtures thereof. Preferably, the blocking agent is a gluconate, more preferably sodium gluconate.

[0038] The component B used contains at least about 0.01% by weight, preferably at least about 0.05% by weight, more preferably at least about 0.1% by weight, and most preferably at least about 1.0% by weight, about 0.01% to about 25% by weight, preferably about 0.05% to about 20% by weight, more preferably about 0.1% to about 15% by weight, and most preferably about 1.0% to about 10% by weight of the blocking agent, based on the total weight of component B. In a most preferred embodiment, component B contains about 0.2 to about 0.4% by weight of sodium gluconate, based on the total weight of component B.

[0039] The water content in component B is at least about 1% by weight, preferably at least about 5% by weight, more preferably at least about 10% by weight, and most preferably at least about 20% by weight, from about 1% by weight to about 50% by weight, preferably from about 5% by weight to about 40% by weight, more preferably from about 10% by weight to about 30% by weight, and most preferably from about 15% by weight to about 25% by weight, based on the total weight of component B.

[0040] Inorganic mortar systems consist of calcium aluminate cement (CAC), granulated blast furnace slag (GGBFS), and calcium sulfate (CaSO 4It has been found that rapid ettringite formation occurs during hydration when the concrete contains a mixture of calcium aluminate and calcium sulfate. In concrete chemistry, the reaction of calcium aluminate with calcium sulfate produces the compound with the general formula (CaO) 6 (Al 2 O 3 )(SO 3 ) 3 32 H 2 O or (CaO) 3 (Al 2 O 3 )(CaSO 4 ) 3 32H 2 Hexacalcium aluminate trisulfate hydrate, represented by O, is formed, resulting in rapid setting and hardening as well as shrinkage compensation or even expansion.

[0041] The calcium sulfate used in the inorganic mortar system for chemical fixing of anchoring means in mineral substrates according to the invention is in the form of calcium sulfate anhydrite, calcium sulfate hemihydrate or calcium sulfate dihydrate or mixtures thereof. In a preferred embodiment of the invention, the calcium sulfate used is in the form of calcium sulfate hemihydrate.

[0042] The calcium sulfate used in the inorganic mortar system for chemically fixing the anchoring means in the mineral substrate according to the present invention is at least about 5% by weight, preferably at least about 10% by weight, more preferably at least about 15% by weight, and most preferably at least about 20% by weight, about 5% to about 70% by weight, preferably about 10% to about 60% by weight, more preferably about 15% to about 50% by weight, and most preferably about 20% to about 40% by weight of calcium sulfate, based on the total weight of component B.

[0043] The ratio of calcium sulfate to calcium aluminate cement used in the inorganic mortar system for chemical fixing of anchoring means in mineral substrates according to the invention is in the range of 0.01 to 0.25, preferably in the range of 0.05 to 0.15.

[0044] The calcium sulfate used according to the invention is preferably contained in the initiator component B of the inorganic mortar system.

[0045] Preferably, Component B used in the present invention contains at least about 5% by weight, preferably at least about 10% by weight, more preferably at least about 15% by weight, and most preferably at least about 20% by weight, about 5% to about 80% by weight, preferably about 10% to about 70% by weight, more preferably about 15% to about 60% by weight, and most preferably about 20% to about 40% by weight of calcium sulfate, based on the total weight of Component B.

[0046] Component B used in the present invention may optionally contain at least one mineral filler. The mineral filler that may be used in the present invention may be limestone filler, such as calcite, sand, corundum, dolomite, alkali-resistant glass, crushed stone, gravel, gravel, quartz, quartz flour, quartz sand, clay, fly ash, fumed silica, brick powder, rice husk ash, phonolite, calcined clay and metakaolin, carbonate compounds, pigments, titanium dioxide, lightweight fillers, or mixtures thereof. Suitable fillers are commercially available products. Component B may contain at least about 1% by weight, preferably at least about 10% by weight, more preferably at least about 20% by weight, and most preferably at least about 30% by weight of said at least one filler, based on the total weight of component B. The at least one mineral filler contained in component B according to the present invention is preferably a mixture of mineral fillers. The at least one mineral filler is selected to obtain a particle size complementary to the particle size of the aluminous cement and the granulated blast furnace slag.

[0047] In advantageous embodiments, component B further comprises the following properties, alone or in combination:

[0048] Component B may additionally comprise a thickener. The thickener used in the present invention may be selected from the group consisting of bentonite, silicon dioxide, quartz, acrylate-based thickeners such as alkali-soluble or alkali-swellable emulsions, fumed silica, clays, and titanate chelating agents. Mention may be made by way of example of polyvinyl alcohol (PVA), hydrophobically modified alkali soluble emulsion (HASE), hydrophobically modified ethylene oxide urethane polymers known in the art as HEUR, and cellulosic thickeners such as hydroxymethyl cellulose (HMC), hydroxyethyl cellulose (HEC), hydrophobically-modified hydroxy ethyl cellulose (HMHEC), sodium carboxymethyl cellulose (SCMC), sodium carboxymethyl 2-hydroxyethyl cellulose, 2-hydroxypropyl methylcellulose, 2-hydroxyethyl methylcellulose, 2-hydroxybutyl methylcellulose, 2-hydroxyethyl ethylcellulose, 2-hydroxypropyl cellulose, attapulgite clays, and mixtures thereof. Suitable thickeners are commercially available products such as Optigel WX (BYK-Chemie GmbH, Germany), Rheolate 1 (Elementis GmbH, Germany), and Cellosize™, Acrysol ASE-60 (The Dow Chemical Company).Component B contains at least about 0.01 wt. %, preferably at least about 0.05 wt. %, more preferably at least about 0.1 wt. %, and most preferably at least about 0.3 wt. %, from about 0.01 wt. % to about 15 wt. %, preferably from about 0.05 wt. % to about 10 wt. %, more preferably from about 0.1 wt. % to about 5 wt. %, and most preferably from about 0.1 wt. % to about 1 wt. % of the thickener, based on the total weight of component B.

[0049] In a preferred embodiment, Component B may comprise a cellulosic thickener, such as hydroxymethylcellulose (HMC) or hydroxyethylcellulose (HEC).

[0050] Component B may additionally comprise a plasticizer. The plasticizer may be selected from the group consisting of low molecular weight (LMW) polyacrylic acid polymers, superplasticizers from the family of polyphosphonate polyox and polycarbonate polyox, and Ethacryl superplasticizers from the polycarboxylate ether group, and mixtures thereof, such as Ethacryl™ G (Coatex, Arkema Group, France), Acumer™ 1051 (Rohm and Haas, UK), or Sika® ViscoCrete®-20 HE (Sika, Germany). Suitable plasticizers are commercially available products. Component B may contain at least about 0.2 wt %, preferably at least about 0.3 wt %, more preferably at least about 0.4 wt %, and most preferably at least about 0.5 wt %, of the plasticizer in an amount of about 0.2 wt % to about 20 wt %, preferably about 0.3 wt % to about 15 wt %, more preferably about 0.4 wt % to about 10 wt %, and most preferably about 0.5 wt % to about 5 wt %, based on the total weight of component B.

[0051] The presence of plasticizers and thickeners does not change the overall inorganic character of Component B.

[0052] The component B used, which comprises blocked granulated blast furnace slag, is present in the aqueous phase, preferably in the form of a slurry or paste.

[0053] Furthermore, component A and / or component B may contain an accelerator component. The accelerator component is composed of at least one alkali and / or alkaline earth metal salt selected from the group consisting of hydroxides, chlorides, sulfates, phosphates, monohydrogen phosphates, dihydrogen phosphates, nitrates, carbonates, and mixtures thereof, preferably the accelerator component is an alkali or alkaline earth metal salt, more preferably a water-soluble alkali or alkaline earth metal salt, more preferably a calcium metal salt such as calcium hydroxide, calcium sulfate, calcium carbonate, calcium chloride, calcium formate, or calcium phosphate, a sodium metal salt such as sodium hydroxide, sodium sulfate, sodium carbonate, sodium chloride, sodium formate, or sodium phosphate, or a lithium metal salt such as lithium hydroxide, lithium sulfate, lithium sulfate monohydrate, lithium carbonate, lithium chloride, lithium formate, or lithium phosphate, and most preferably lithium sulfate or lithium sulfate monohydrate. Components A and / or B contain at least about 0.01% by weight, preferably at least about 0.05% by weight, more preferably at least about 0.1% by weight, and most preferably at least about 1.0% by weight, of the accelerator in an amount of from about 0.01% to about 25% by weight, preferably from about 0.05% to about 20% by weight, more preferably from about 0.1% to about 15% by weight, and most preferably from about 1.0% to about 10% by weight, based on the total weight of components A or B, respectively.

[0054] It is preferred that the pH value of component B is greater than 10, more preferably greater than 11, most preferably greater than 12, in particular in the range 10-14, preferably in the range 11-13.

[0055] In the most preferred embodiment, component A comprises or consists of the following components: 70-80% by weight calcium aluminate cement, 0.5 to 1.5% by weight of phosphoric acid, 0.5 to 1.5% by weight of a thickening agent, 0.5 to 1.5% by weight of a plasticizer, 0.001 to 0.05% by weight of an antimicrobial or biocide, 15 to 25% by weight of water, Optionally, 0.01% to 5% by weight of lithium sulfate or lithium sulfate monohydrate, and Optionally, 5-20% by weight of mineral filler.

[0056] In the most preferred embodiment, component B comprises or consists of the following components: 20% to 50% by weight of granulated blast furnace slag; 5.0% to 50% by weight of calcium sulfate, 0.1 to 0.5% by weight of sodium gluconate, 10-30% by weight of at least one mineral filler, 0.01% to 0.5% by weight of a thickening agent, 0.5 to 1.5% by weight of a plasticizer, 15% to 30% by weight of water, and Optionally, 0.1% to 5% by weight of lithium sulfate or lithium sulfate monohydrate.

[0057] Component A of the present invention can be prepared as follows: A phosphorus-containing blocking agent is mixed with water such that the pH value of the resulting mixture is about 2. A plasticizer is added and the mixture is homogenized. Alumina cement, optionally calcium sulfate, and optionally mineral filler are premixed and gradually added to the mixture with increasing stirring speed such that the pH value of the resulting mixture is about 4. Finally, the thickener and antimicrobial / biocide, and optionally accelerator components are added and mixed until the mixture is completely homogenous.

[0058] Component B of the present invention can be prepared as follows: the plasticizer, blocking agent, and thickener are mixed with water, followed by stepwise addition of granulated blast furnace slag, calcium sulfate, and filler with increasing stirring speed until the mixture is homogenous. Finally, optional accelerator components may be added until the mixture is completely homogenous.

[0059] Components A and B are present in the aqueous phase, preferably in the form of a slurry or paste. In particular, components A and B have a pasty to fluidic appearance according to their respective compositions. In a preferred embodiment, components A and B are in the form of a paste, thereby preventing sagging when mixing the two components.

[0060] The weight ratio between component A and component B (A / B) is preferentially comprised between 7 / 1 and 1 / 3, preferably 3 / 1. Preferably, the composition of the mixture comprises 75% by weight of component A and 25% by weight of component B. In an alternative embodiment, the composition of the mixture comprises 25% by weight of component A and 75% by weight of component B.

[0061] The inorganic system is mineral in nature and is not affected by the presence of additional thickeners or other agents.

[0062] The shelf life of the inorganic system depends on the individual shelf life of each of the respective components, in particular components A and B, which have a shelf life of at least 6 months at ambient temperature to protect the system from storage and delivery delays. Most preferably, components A and B are individually stable for at least 6 months. Components A and B were stored in closed containers at 20°C to avoid water evaporation and were checked for flowability, homogeneity, whether sedimentation occurs, and any changes in pH value after several time intervals. The properties of all components remained unaffected after 6 months, so the shelf life is at least 6 months at 20°C.

[0063] After mixing of the two components A and B, it is preferred that the inorganic mortar system has an initial setting time of at least 5 minutes, preferably at least 10 minutes, more preferably at least 15 minutes, most preferably at least 20 minutes, in particular in the range of about 5 to 25 minutes, preferably in the range of about 10 to 20 minutes.

[0064] In multi-component mortar systems, especially inorganic mortar systems, the volume ratio of cementitious component A to initiator component B is between 1:1 and 7:1, preferably 3:1. In an alternative embodiment, the volume ratio of cementitious component A to initiator component B is between 1:3 and 1:2.

[0065] After being produced separately, components A and B are introduced into separate containers, from which they are discharged by a mechanical device and conducted through a mixing device. The mineral mortar system of the invention is preferably a ready-to-use system, in which components A and B are placed separately from each other in a multi-chamber device, such as a multi-chamber cartridge and / or a multi-chamber cylinder, or in a mineral capsule, preferably in a two-chamber cartridge or in a mineral capsule. The multi-chamber system preferably comprises two or more foil bags for separating the cured type component A and the initiator component B. The contents of the chambers or bags, which are mixed together by the mixing device, preferably via a static mixer, can be injected into the borehole. It is also possible to assemble in a set of multiple chamber cartridges or pails or buckets.

[0066] The settable alumina cement composition leaving the static mixer is inserted directly into the borehole where it is needed to fix the anchoring means and where the mineral matrix is ​​first introduced during the chemical fixation of the anchoring means, after which the construction elements to be fixed, such as anchor rods, are inserted and adjusted, after which the mortar composition sets and hardens. In particular, the inorganic system of the present invention is considered as a chemical anchor for fixing anchoring means, in particular metal elements.

[0067] The inorganic mortar system comprising calcium sulfate of the present invention can be used for the chemical fixation of anchoring means, preferably metal elements such as anchor rods, especially threaded rods, bolts, steel reinforcements, in mineral substrates such as brickwork, concrete, permeable concrete or structures made of natural stone. In particular, the inorganic mortar system of the present invention can be used for the chemical fixation of anchoring means such as metal elements in boreholes. It can be used for fixing purposes that include increasing the load capacity at temperatures above room temperature or at elevated temperatures and / or increasing the bond stress in the cured state.

[0068] In particular, the inorganic mortar system of the invention is used in a method for chemically fixing an anchoring means in a mineral substrate, comprising the steps of introducing a borehole into the mineral substrate, mixing component A with component B to obtain a settable alumina cement composition, inserting said alumina cement composition directly into the borehole, inserting and adjusting the construction element to be fixed, and allowing the alumina cement composition to harden and set.

[0069] Furthermore, the inorganic mortar system of the present invention may be used for coating or for attaching fibers, scrims, fabrics or composites, especially high modulus fibers, preferably carbon fibers, in particular for the reinforcement of building structures, for example walls or ceilings or floors, or even for placing components, such as plates or blocks made of stone, glass or plastic, on buildings or construction elements.

[0070] The following examples illustrate the invention without, however, limiting it thereto. EXAMPLES

[0071] 1. Preparation of Components A and B First, the cementitious component A and the initiator component B are prepared by mixing the components specified in Tables 1 and 2, respectively. The percentages given are expressed in weight percent.

[0072] Specifically, 19.48 grams of deionized water, 0.75 grams of 85% phosphoric acid (blocking agent), 0.6 grams of Ethacryl G (superplasticizer), and 0.02 grams of Nuosept® (biocide) were homogenized at room temperature, and calcium aluminate cement (78.50 grams, pure Ternal White®) was added in small portions one after another while stirring with a dissolver, finally obtaining a smooth liquid paste-like slurry of blocked cement in water with a pH of less than 7. After the calcium aluminate cement was added, 0.15 grams of lithium sulfate monohydrate and 0.5 grams of xanthan gum (thickener) were added, and the slurry was homogenized at 2500 rpm for 5 minutes.

[0073] [Table 1]

[0074] A typical preparation of component B is as follows: 1.0 grams of Ecodis® P50 (plasticizer), 0.1 grams of Cellosize® QP-100MH (thickener), and 0.22 grams of sodium gluconate were dissolved in 21.00 grams of deionized water. While stirring in a dissolver, 50 grams of granulated blast furnace slag, 10 grams of sand, and 5 grams of Betocarb UF were added with vigorous stirring. Then, the respective amounts of calcium sulfate hemihydrate (Keramod 125) were added and stirred to finally obtain a smooth liquid paste-like slurry of solids in water with a pH greater than 11.

[0075] [Table 2]

[0076] 2. Mechanical Performance Determination After preparation, binder component A and each B component were filled into separate chambers of inorganic plastic hard cartridges in a defined ratio of component A:B=3:1. The hard cartridges were placed in a dispenser, a static mixer was attached, the mortar was poured into a steel sleeve, and a threaded rod (M8) was inserted. The steel sleeve was 28 mm deep and 10 mm in diameter. The pull-out strength was measured after a certain curing time to measure the improvement in performance over the curing time of the mortar. The ultimate breaking load was calculated as the bond strength and is shown in Table 3 in N / mm 2 Shown in units.

[0077] [Table 3]

[0078] Table 3 shows that when a blocked slag slurry containing calcium sulfate is mixed with a blocked aluminate slurry, increased load values ​​can be achieved already within 24 hours of curing. From the results shown it can be clearly seen that the use of calcium sulfate in the blocked slag slurry significantly increases the bond strength already after 24 hours, allowing for earlier loading and exhibiting a higher load capacity compared to the system without calcium sulfate.

[0079] As shown above, the inorganic mortar system of the present invention offers a comparable curing rate and mechanical strength to systems known in the art, but its essentially mineral composition makes it much less toxic than known systems of the prior art, much less polluting to the environment and allowing for cost-effective production.

[0080] Furthermore, the addition of calcium sulfate to such systems has been shown to induce the formation of the bulky hydrate phase ettringite, which opposes shrinkage. The formation of ettringite by adding a calcium sulfate source also reduces conversion because monosulfates are formed, which are more stable than calcium aluminate hydrates formed at low and moderate temperatures. In addition, binders that maintain a low water-to-cement ratio exhibit higher strength and better durability compared to mortars possessing a high water-to-cement ratio due to their denser microstructure.

[0081] Adding calcium sulfate to the blocked slag slurry does not impair the storage stability of the slurry and allows further ettringite formation after mixing with aluminous cement, which compensates for the shrinkage of the mortar, gives higher pull-out strength, and also improves durability due to volumetric stability (no shrinkage cracking).

[0082] Advantageously, it has been demonstrated that granulated blast furnace slag, a waste product from iron and steel production and therefore a cheap alternative with a low carbon dioxide footprint, can be used in inorganic fixation systems when reused as a binder and additionally calcium sulfate.

[0083] Furthermore, the inorganic mortar system of the present invention has been shown to contain no harmful substances, while maintaining the standards for chemical bonding applications, and therefore also includes reduced carbon dioxide emissions and labeling. In addition, the use of granulated blast furnace slag in particular has been shown to be more sustainable compared to the use of common Portland cement, and also has a lower carbon dioxide emissions than synthetic resins.

Claims

1. 1. Use of calcium sulfate in an inorganic mortar system comprising a cured aqueous phase aluminous cement component A and an initiator component B in the aqueous phase for starting the curing process, wherein component A further comprises at least one blocking agent selected from the group consisting of boric acid, phosphoric acid, metaphosphoric acid, phosphorous acid, and phosphonic acid, and water, and component B comprises blocked granulated blast furnace slag, water, and optionally at least one mineral filler.

2. 2. Use according to claim 1, wherein the calcium sulfate is in the form of calcium sulfate anhydrous, calcium sulfate hemihydrate or calcium sulfate dihydrate or mixtures thereof, preferably in the form of calcium sulfate hemihydrate.

3. 3. Use according to claim 1 or 2, wherein the ratio of calcium sulfate to calcium aluminate cement is in the range of 0.01 to 0.25, preferably in the range of 0.05 to 0.

15.

4. The use according to any one of claims 1 to 3, wherein said calcium sulfate is comprised in said initiator component B of said inorganic mortar system.

5. The use according to any one of claims 1 to 4, wherein the blocked granulated blast furnace slag comprises granulated blast furnace slag, and the blocking agent for the granulated blast furnace slag is selected from the group consisting of gluconic acid, glycolic acid, phosphonic acid, their salts and esters, glucose, and mixtures thereof.

6. The use according to any one of claims 1 to 5, wherein the granulated blast furnace slag is present in the range of about 10% by weight to about 70% by weight based on the total weight of component B.

7. The use according to any one of claims 1 to 6, wherein the blocking agent for the granulated blast furnace slag is present in the range of about 0.05% to about 20% by weight based on the total weight of component B.

8. The use according to any one of claims 1 to 7, wherein the blocking agent is sodium gluconate.

9. Use according to any one of claims 1 to 8, wherein component B comprises a thickener, preferably a cellulosic thickener, such as hydroxymethylcellulose or hydroxyethylcellulose.

10. 10. The use according to any one of claims 1 to 9, wherein the at least one mineral filler in component B is limestone filler, sand, corundum, dolomite, alkali-resistant glass, crushed stone, gravel, gravel, quartz, quartz flour, quartz sand, clay, fly ash, fumed silica, brick flour, rice husk ash, phonolite, calcined clay and metakaolin, carbonate compounds, pigments, titanium dioxide, lightweight fillers, or mixtures thereof.

11. The use according to any one of claims 1 to 10, wherein component A and component B have a shelf life of at least 6 months.

12. The use according to any one of claims 1 to 11, wherein component A and component B are in the form of a slurry or paste.

13. The use according to any one of claims 1 to 12, wherein the pH value of component B is greater than 10.

14. Component B is 20% to 50% by weight of granulated blast furnace slag; 5.0% to 50% by weight of calcium sulfate, 0.1 to 0.5% by weight of sodium gluconate, 10-30% by weight of at least one mineral filler, 0.01% to 0.5% by weight of a thickening agent, 0.5 to 1.5 wt. % of a plasticizer, 15% to 30% by weight of water, and 14. Use according to any one of claims 1 to 13, optionally comprising 0.1% to 5% by weight of lithium sulphate or lithium sulphate monohydrate.

15. Use of the inorganic mortar system according to any one of claims 1 to 14 for chemically fixing an anchoring means in a mineral substrate.

16. A method for chemically fixing anchoring means in mineral substrates, characterized in that an inorganic mortar system containing calcium sulfate is used, said inorganic mortar system comprising a cured aqueous phase alumina cement component A and an initiator component B in the aqueous phase for starting the curing process, component A further comprising at least one blocking agent selected from the group consisting of boric acid, phosphoric acid, metaphosphoric acid, phosphorous acid and phosphonic acid, and water, component B comprising blocked granulated blast furnace slag, water and optionally at least one mineral filler, said method comprising: - introducing a borehole into the mineral matrix; - mixing component A with component B to obtain a hardenable alumina cement composition; - inserting the alumina cement composition directly into the borehole; - inserting and adjusting the construction elements to be fixed; - allowing the alumina cement composition to harden and set.

Citation Information

Patent Citations

  • Method for preventing solidification of granulated blast furnace slag

    JP2015054807A

  • Retention system and its use

    JP2018534228A

  • Stabilized aqueous composition for initiating setting and hardening of alumina cement composition

    JP2018536609A

  • Two-component mortar fastening materials based on aluminous cement and their use.

    JP2019500297A

  • Multi-component mortar

    JP2019536725A